Balloon angioplasty of aortic coarctation in critically ill newborns using axillary artery access - Giovanni Meliota; Maristella Lombardi; Pierluigi Zaza; Maria Rosaria Tagliente; Ugo Vairo (Wolters Kluwer Medknow Publications, 2020)
Balloon angioplasty may be performed as the first treatment of aortic coarctation to stabilize newborns too sick for immediate surgery. The issue of vascular access is the key to the successful treatment of critical newborns. In our study, we argue that the lesser-known axillary access route is the safest and most effective route of vascular access for balloon angioplasty in infants with aortic coarctation. To support this argument, we present the case of eight unstable newborns with complex heart diseases, who were successfully treated with percutaneous intervention through the axillary artery. This case series is followed by an analysis of the greater efficacy of this technique compared to the more conventional femoral and carotid routes. We conclude by acknowledging the substantial advantages of this lesser-known vascular access and advocate its more widespread clinical implementation in the treatment of critical newborns.